Intervention culture, grouping and triage: high-stakes tests and practices of division in English primary schools. Issue 2 (23rd January 2021) - Bradbury, Alice; Braun, Annette; Quick, Laura
Abstract: This paper explores the practices of division in operation in primary schools in England in response to the pressures of high stakes tests at age 10/11, known as SATs. Using data from interviews with 20 primary headteachers and information from a survey of nearly 300 primary heads, we argue that the organisation of pupils in preparation for SATs involves 1) the use of grouping by 'ability' in sets, despite the increasing evidence of the disadvantages; 2) forms of educational triage, where borderline or 'cusp' children are prioritised, and more complex forms of 'double triage'; and 3) the growth of 'intervention culture' where some children are withdrawn from normal lessons to resolve 'gaps' in their learning. In this article these practices are understood through a Foucauldian lens as micropractices of power which label and categorise pupils within an accountability system that seeks to classify pupils on a norm/Other binary.